Electrocardiographic Risk Markers of Cardiac Death: Gender Differences in the General Population - Haukilahti, Mira Anette E.; Kenttä, Tuomas V.; Tikkanen, Jani T.; Anttonen, Olli; Aro, Aapo L.; Kerola, Tuomas; Eranti, Antti; Holkeri, Arttu; Rissanen, Harri; Heliövaara, Markku; Knekt, Paul; Junttila, M. Juhani; et al. (Frontiers in Physiology, 2021)
Background Cardiac death is one of the leading causes of death and sudden cardiac death (SCD) is estimated to cause approximately 50% of cardiac deaths. Men have a higher cardiac mortality than women. Consequently, the mechanisms and risk markers of cardiac mortality are not as well defined in women as they are in men. Aim The aim of the study was to assess the prognostic value and possible gender differences of SCD risk markers of standard 12-lead electrocardiogram in three large general population samples. Methods The standard 12-lead electrocardiographic (ECG) markers were analyzed from three different Finnish general population samples including total of 20,310 subjects (49.9% women, mean age 44.8 ± 8.7 years). The primary endpoint was cardiac death, and SCD and all-cause mortality were secondary endpoints. The interaction effect between women and men was assessed for each ECG variable. Results During the follow-up (7.7 ± 1.2 years), a total of 883 deaths occurred (24.5% women, p < 0.001). There were 296 cardiac deaths (13.9% women, p < 0.001) and 149 SCDs (14.8% women, p < 0.001). Among those who had died due to cardiac cause, women had more often a normal electrocardiogram compared to men (39.0 vs. 27.5%, p = 0.132). After adjustments with common cardiovascular risk factors and the population sample, the following ECG variables predicted the primary endpoint in men: left ventricular hypertrophy (LVH) with strain pattern (p < 0.001), QRS duration > 110 ms (p < 0.001), inferior or lateral T-wave inversion (p < 0.001) and inferolateral early repolarization (p = 0.033). In women none of the variables remained significant predictors of cardiac death in multivariable analysis, but LVH, QTc ≥ 490 ms and T-wave inversions predicted SCD (p < 0.047 and 0.033, respectively). In the interaction analysis, LVH (HR: 2.4; 95% CI: 1.2–4.9; p = 0.014) was stronger predictor of primary endpoint in women than in men. Conclusion Several standard ECG variables provide independent information on the risk of cardiac mortality in men but not in women. LVH and T-wave inversions predict SCD also in women.